Follow the leader (or not): The influence of peer CEOs' characteristics on interorganizational imitation - Gupta, Abhinav; Misangyi, Vilmos F. (Strategic Management Journal, 2018)
[Research Summary: We argue that because charisma and narcissism represent widely held prototypes of effective and ineffective forms of leadership, respectively, the likelihood that a focal firm will imitate the practices of its peer firms is affected by these peer firms' CEO characteristics. We theorize that peer firm CEO charisma enhances the focal firm's imitation of peer firms' behaviors, while peer firm CEO narcissism diminishes it. We further posit that the uncertainty of the context affects these imitation processes: industry dynamism and prior experience in a given strategic domain, respectively, strengthens and dampens focal firms' susceptibility to these peer CEOs' attributes. We test and find support for these ideas using a longitudinal sample of Fortune 500 firms in two distinct domains, corporate strategy and corporate social responsibility. Managerial Summary: When companies are uncertain about the costs and benefits of strategic actions this may lead them to imitate the actions of peer companies. But given the uncertainty, the challenge for executives is: which companies to emulate and which to ignore? In a sample of Fortune 500 companies, we find that the charisma or narcissism of a peer company's CEO positively or negatively influences, respectively, the degree to which the peer company's strategic actions are imitated. We reason that this is because these particular CEO attributes are widely believed to drive leadership effectiveness or ineffectiveness, respectively. We also find that the effects of these CEO characteristics on imitation are stronger in dynamic industry environments and weaker for companies that already have experience with the given strategy.]